Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Pusat Atribut Bagugu Law School (BLS) Jakarta Barat: The Effect of Price and Service Quality on Customer Satisfaction at the Bagugu Law School (BLS) Attribute Center in West Jakarta - Lilis Santri Duha; Darma Wijaya; Fadli Ilyas (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This research aims to ainalyze thei influence of price and service quality on customer satisfaction at Bagugu Law School (BLS) Attribute Center, West Jakarta. This research uses a quantitative method with an associative approach. The population in ths study includes all consumers who use legal attribute services at Bagugu Law School (BLS) Attribute Center, with ai sample of 40 respondents selected using random sampling technique. Data collecton techniques include interviews, observations, and questionnaires. Data analysis uses validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results show that: (1) Price has a positive and significant effect on customer satisfaction with t count 1.765 > t table 1.686; (2) Service quality does not significantly affect customer satisfaction with t count 1.254 < t table 1.686; (3) Simultaneously, price and service quality have a positive and significant effect on customer satisfaction with f count 245.559 > f table 3.245 and significance value 0.000 < 0.05. Thei coefficient of determination value (Adjusted R Square) of 0.926 indicates that 92.6% of customer satisfaction is influenced by price and service quality, while the remaining 7.4% is influenced by other factors outside this research.